Students’ Responses toward Scientific Argumentation with ADI Learning Model to Physics Literacy: A Case of Indonesian Senior High School Students - Della Shinta Bestiantono (Indonesia Approach Education, 2020)
The aim of this study is to explore Indonesian students’ responses towards scientific argumentation with ADI learning model to physics literacy by using survey study. The sample included 100 Indonesian senior high school students (47% male and 53% female) who were studying at public school in East Java province. The Responses towards Scientific Argumentation ADI Learning Model to Physics Literacy (RT-SAPL) questionnaire was developed with Indonesian language and validated through an exploratory factor analysis of participants’ responses. For measuring the correlation among three dimensions of scale, the Pearson Correlation product moment was used. The findings indicated: the instrument used in this study had satisfactory validity and reliability. Meanwhile, the construct validities of the RT-SAPL were varying from .617 and .832 and extracting 70.655% of the variance with overall Cronbach’s alpha constant was .854. Moreover, the dimension of ADI learning model came in the first rank and followed by Scientific argumentation as well as the degree of responses towards scientific argumentation with ADI learning model to physics literacy. Finally, the findings have also indicated a significant relationship among factors of RT-SAPL.